Superfamilies SDR and MDR: from early ancestry to present forms. Emergence of three lines, a Zn-metalloenzyme, and distinct variabilities. - Jörnvall, H; Hedlund, J; Bergman, T; Oppermann, U; Persson, B (2010)
Two large gene and protein superfamilies, SDR and MDR (short- and medium-chain dehydrogenases/reductases), were originally defined from analysis of alcohol and polyol dehydrogenases. The superfamilies contain minimally 82 and 25 genes, respectively, in humans, minimally 324 and 86 enzyme families when known lines in other organisms are also included, and over 47,000 and 15,000 variants in existing sequence data bank entries. SDR enzymes have one-domain subunits without metal and MDR two-domain subunits without or with zinc, and these three lines appear to have emerged in that order from the universal cellular ancestor. This is compatible with their molecular architectures, present multiplicity, and overall distribution in the kingdoms of life, with SDR also of viral occurrence. An MDR-zinc, when present, is often, but not always, catalytic. It appears also to have a structural role in inter-domain interactions, coenzyme binding and substrate pocket formation, as supported by domain variability ratios and ligand positions. Differences among structural and catalytic zinc ions may be relative and involve several states. Combined, the comparisons trace evolutionary properties of huge superfamilies, with partially redundant enzymes in cellular redox functions.